A Review on Conservation and Population Status of Lion Tailed Macaque - Tanzeem Azeeza S.; Leelavathi , D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The lion-tailed macaque is a critically endangered species. They are only found in the Western Ghats. Threats to these endangered species over time have included encroachments, road deaths, poaching, and climate change. The survival of this one-of-a-kind species is directly related to environmental degradation and destruction. An astonishing fact checks revealed by IUCN states that there are about 2400-2500 Lion Tailed Macaque in the world. According to recent reports in the daily "THE HINDU," Valparai in Tamil Nadu may be the last remaining home for Lion Tailed Macaques. Appropriate conservation techniques, demographic research, and educational campaigns on these species could aid in their survival. The review study was carried out to find out the conservation gap and population assessment of the species over the years. In order for the species to survive the natural habitats should be proposed as the conservation site.